The invisibles : stories - Sheehy, Hugh, 1979- (Flannery O'Connor Award for Short Fiction., 2012)
Though Hugh Sheehy's often tragic, sometimes gruesome stories feature bloodied knives and mysterious disappearances, at the heart of these thoughtful thrillers are finely crafted character studies of people who wrestle with the darker aspects of human nature-grief, violence, loneliness, and the thoughts of crazed minds. Sheehy's stories shine a spotlight on the bleak fringes of America, giving voice to the invisibles who need it most. A dismal assistant teacher spiking her coffee after school is suddenly locked in a basement with a student who has just witnessed his father's murder. A seventeen-year-old girl at a skate rink whose name no one can remember is motherless, friendless, and sure she will be the next to go. The heartbroken victim of a miscarriage dreams of her fetus's voyage through the earth's plumbing. The estranged addict son, certain of his innate goodness, loses himself in a blizzard and fails his family again. Sheehy's characters learn that however invisible they may feel and whatever their intentions, their actions incur a cost both to themselves and those around them. They struggle to tame or come to terms with the forces they meet-the tragedies-that are far larger than their small existences. In this debut, Sheehy illuminates the all-but-silent note of adult loneliness and how we cope with it or, perhaps, just move past it.